Assessment of ozone (o3) injury on foliage of (syzygium myrtifolium) and other selected tree species in Bintulu - Muhammad Shabri Salamat
The study was conducted due to the increasing of 0zone (03) concentration in atmosphere that has cause effect on humans, vegetation and materials. The objectives of the study were to assess the extent of O3 injury, abiotic and biotic injury on foliage Syzygiun myrtifolium and other selected tree species. Besides, to assess the physiological growth effects and the concentration of polluted O3 on leaves of Syzygium myrtifolium and other selected trees in Bintulu. This research vwas carried out for six months from October 2016 until March 2017 to find the ozone (O3) injury on foliage of Syzygium myrtifolium and other selected tree species as the planting material. For this experiment, the using of all factors including biotic and abiotic factor was determined through the sample tree. In addition, the assessment of physiological growth effects also was determined in this study using the same planting material. The chlorophyll content, leaf area index (LAI), total number of leaves, and weight of wax content were measured as the parameter of this